2020
DOI: 10.1186/s12864-020-07258-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs conferring resistance to scald (Rhynchosporium commune) in the barley nested association mapping population HEB-25

Abstract: Background Barley scald, caused by the fungus Rhynchosporium commune, is distributed worldwide to all barley growing areas especially in cool and humid climates. Scald is an economically important leaf disease resulting in yield losses of up to 40%. To breed resistant cultivars the identification of quantitative trait loci (QTLs) conferring resistance to scald is necessary. Introgressing promising resistance alleles of wild barley is a way to broaden the genetic basis of scald resistance in cultivated barley. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 98 publications
(187 reference statements)
2
13
0
Order By: Relevance
“…The recurrent parent in HEB-25 is ‘Barke’, which was crossed with 25 wild barley ( H. spontaneum ) accessions from the fertile crescent and thus having clearly higher amount of diversity introduced in their material compared to ours. Interestingly, out of the eight QTL Büttner et al ( 2020 ) found two others in addition to QRs7H.2, which are potentially the same as ours: the one considered as Rrs1 on chromosome 3H and possibly the QTL on 6H at 18.9Mbp.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The recurrent parent in HEB-25 is ‘Barke’, which was crossed with 25 wild barley ( H. spontaneum ) accessions from the fertile crescent and thus having clearly higher amount of diversity introduced in their material compared to ours. Interestingly, out of the eight QTL Büttner et al ( 2020 ) found two others in addition to QRs7H.2, which are potentially the same as ours: the one considered as Rrs1 on chromosome 3H and possibly the QTL on 6H at 18.9Mbp.…”
Section: Discussionsupporting
confidence: 81%
“…The other QTL detected in MAGIC 4 in our study had its peak marker on the long arm of chromosome 7H at 635.2 Mb, which is close to Rrs15 located at 647.6 Mb (Genger et al 2003). An even closer QTL is the recently reported new QTL QRs7H.2 624.2 Mb, which was found by Büttner et al (2020) in a barley nested association mapping population, HEB-25 (Maurer et al 2015). QTL close to the significant marker can be considered as very relevant candidates.…”
Section: Known Scald Resistance Qtl Detected Among the Populationsmentioning
confidence: 74%
“…These studies used three, five, and two field trials, respectively, for their GWAS analysis. A further eight QTL originating from wild barley accessions were identified by GWAS in the Nested Association Mapping population HEB-25 [21]. GWAS was also used to map nine rhynchosporium resistance regions, including three new regions, in four multi-parent advanced generation inter-cross (MAGIC) populations tested in northern Europe [22].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a limited number of resistance genes in barley against R. commune have been identified, with Rrs18, found on chromosome 6HS by Hofmann (2014) and confirmed by Coulter et al (2018) being the most recently reported. A number of these Rrs genes originate from landraces (Bjørnstad et al 2004;Hanemann et al 2010;Hofmann et al 2013). It is suggested that Scandinavian and other northern European landraces might be a prime source for resistance to rhynchosporium as it is speculated that R. commune originated in this area providing diverse R. commune populations and the longest period of landrace selection for rhynchosporium resistance (McDonald 2015), suggesting the Scottish barley landrace population 'Bere' as a suitable candidate.…”
Section: Introductionmentioning
confidence: 99%